Association between pediatric TBI and mental health and substance use disorders: A scoping review. (12th May 2023) - Adams (Nejatbakhsh), Nasrin; Dawson, Danielle; Hutchison, Mark; Selby, Peter
ABSTRACT: Background: The relationship between pediatric Traumatic Brain Injury (TBI) and long-term mental health and substance use disorders is not well known, resulting in inadequate prevention and management strategies. The aim of this scoping review is to review the evidence on pediatric TBI and the development of mental health disorders and substance use later in life and to identify gaps in the literature to inform future research. Methods: We searched multiple databases for original articles published between September 2002 and September 2022 on TBI-related mental health and/or substance use disorders in children and youth. Two independent reviewers performed the screening using Arksey and O'Malley and Levac et al.'s scoping review framework. Results: A total of six papers are included in this scoping review. Studies included are comprised of cross-sectional and prospective longitudinal cohort studies. Discussion: A correlation between pediatric TBI and development of certain mental health disorders and substance use is suggested, although much of the current evidence is mixed and does not account for confounding variables. Future studies should aim to closely examine these links and identify modifiers that can influence these relationships.